The effects of online stimuli on consumers' purchase intention : a comparative study of different internet platforms - Attasit Patanasiri; Donyaprueth Krairit; Vatcharaporn Esichaikul; Supasith Chonglerttham (Pathum Thani, Thailand : Asian Institute of Technology, 2020)
The aim of this research is to answer the research question of whether consumers of online stores on social-based B2C e-commerce platforms think and act differently than the consumers of Web-based B2C e-commerce platforms and, if so, which metrics can be used to capture these differences. The main research model is constructed according to the Stimulus-Organism-Response model (S-O-R model). Additionally, this research is one of the first empirical studies that employs the S-O-R model as a main research model to explore online users{u2019} behavior. The results of the study demonstrate six findings which contrast with the previous literature. For the first and second findings, the two-way communication tools provided by Web-based and social-based B2C e-commerce platforms are not powerful enough to significantly affect the emotional needs of online consumers and the users{u2019} interpretation of online information. The third finding demonstrates that the risk perceived by consumers of both platforms in contemplating a particular purchase action does not significantly affect the emotional needs of consumers. The fourth finding demonstrates that the ability of both platforms to enhance user participation in the platforms{u2019} activities does not significantly affect the users{u2019} curiosity aroused while interacting with the platforms. The fifth finding demonstrates that consumers{u2019} emotional needs do not significantly affect online consumers{u2019} purchase intention with both platforms. The sixth finding demonstrates that the degree of users{u2019} attention while using both platforms does not significantly affect consumers{u2019} purchase intention.
Thesis (Ph.D.) - Asian Institute of Technology, 2020
A dissertation submitted in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Management, School of Management
Keywords: Consumers' preferences; Consumer behavior; Online social networks -- Marketing